Interplanetary manned flights in the context of the 4th Space Program of Ukraine - Азарсков, В.М.; Поліщук, С.Т. (Proceedings of National Aviation University (archive), 2007)
Problems of pilot interplanetary and the possibility of Ukraine’s participation in international programs of space investigation are analyzed